2005
DOI: 10.1152/japplphysiol.00813.2004
|View full text |Cite
|
Sign up to set email alerts
|

Ten-day endurance training attenuates the hyperosmotic suppression of cutaneous vasodilation during exercise but not sweating

Abstract: It is well known that hyperosmolality suppresses thermoregulatory responses and that plasma osmolality (P(osmol)) increases with exercise intensity. We examined whether the decreased esophageal temperature thresholds for cutaneous vasodilation (TH(FVC)) and sweating (TH(SR)) after 10-day endurance training (ET) are caused by either attenuated increase in P(osmol) at a given exercise intensity or blunted sensitivity of hyperosmotic suppression. Nine young male volunteers exercised on a cycle ergometer at 60% pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 28 publications
4
30
0
Order By: Relevance
“…It also improves the responses of SkBF and sweat rate to increased core body temperature during exercise [11,16,17]. Indeed, an increase in cardiac stroke volume and also the sensitivity of increase in SkBF to increased T es during exercise in a warm condition (T a , 30°C) was closely correlated to a PV expansion by a 10-day endurance training (60% VO 2max for 1 h/day at 30°C) [28]. Additionally, Goto et al [43] reported the influences of protein and carbohydrate (CHO) supplementation just after exercise (Pro-CHO; 0.36 g protein/kg and 3.6 kcal) during the 5-day training period (70% VO 2max for 30 min/day) in a warm environment (T a , 30°C) on PV and thermoregulatory responses.…”
Section: Effects Of Exercise Training On Thermoregulation In Warm Andmentioning
confidence: 95%
See 1 more Smart Citation
“…It also improves the responses of SkBF and sweat rate to increased core body temperature during exercise [11,16,17]. Indeed, an increase in cardiac stroke volume and also the sensitivity of increase in SkBF to increased T es during exercise in a warm condition (T a , 30°C) was closely correlated to a PV expansion by a 10-day endurance training (60% VO 2max for 1 h/day at 30°C) [28]. Additionally, Goto et al [43] reported the influences of protein and carbohydrate (CHO) supplementation just after exercise (Pro-CHO; 0.36 g protein/kg and 3.6 kcal) during the 5-day training period (70% VO 2max for 30 min/day) in a warm environment (T a , 30°C) on PV and thermoregulatory responses.…”
Section: Effects Of Exercise Training On Thermoregulation In Warm Andmentioning
confidence: 95%
“…The increased SkBF and sweating responses are characterized by the early start of cutaneous vasodilation and sweating responses to increased T es [28,29] and the increased sensitivity to increase SkBF and sweat rate in response to an increased T es compared with before exercise training [28,29]. It is suggested that the mechanisms of the increase in thermoregulatory responses with exercise training are similar to those following acclimations to repeated heat exposures, including adaptations of the thermoregulatory center and thermoregulatory effectors [1,12] as well as an increase in VO 2max [30] and PV [28,31,32].…”
Section: Effects Of Exercise Training On Thermoregulation In Warm Andmentioning
confidence: 99%
“…5). Since the reduction in each subject was significantly correlated with the increase in PV after training, they suggested that the stretch of baroreceptors due to PV expansion 57,58) was involved in the reduction. However, they also suggested that there was no causal relationship between the reduction in osmotic suppression of cutaneous vasodilation and plasma expansion but they were caused by different mechanisms associated with heat acclimation.…”
Section: Blunted Hyperosmotic Suppressions Of Thermoregulatory Responsesmentioning
confidence: 99%
“…The increased SkBF and sweating responses are characterized by the low T es threshold for cutaneous vasodilation and sweating 57,58) and their enhanced sensitivity to increased T es 57,59) . The magnitude of adaptation depends on the intensity, duration, and frequency of heat exposures, but the most effective maneuver to acquire the adaptation should include 'exercise in the heat' 56) .…”
Section: Improvements Of Thermoregulationmentioning
confidence: 99%
See 1 more Smart Citation